Comparative Study of Judicial Pardon in the Substantive Criminal Law and Criminal Procedure Law of the Netherlands and Indonesia: Note to the Draft Criminal Procedure Code - Moeliono, Tristam Pascal; Hardinanto, Aris (Universitas Muhammadiyah Purwokerto, 2025)
The ruling on Rechterlijk Pardon (judicial pardon) or passing sentence of guilt without imposing penal sanction is regulated in Article 54 paragraph (2) of Law No. 1 of 2023 concerning Criminal Code. On the other hand, various academic drafts of the Criminal Procedure Law, and draft of the Criminal Procedure Law dated March 21, 2023, did not contain a ruling on the same. Meanwhile, the draft of criminal procedure code dated February 17, 2025, March 3, 2025, March 15, 2025, and March 20, 2025 mentions this legal institution only in passing. The legal lacunae resulting from this disharmony consequently make it impossible the passing such a sentence in practice. Numerous legal academic writings on Judicial Pardon can be found written by Indonesian legal scholars, but none seems to focus on the legal history of this institution using primary legal sources and none of those articles refers to most recent draft criminal procedure code. Moreover, those articles still refer to the old criminal code and criminal procedure code draft. The method used in this research is legal normative, using statutory approach as well as comparative law. The main argument here is that the ruling about judicial pardon should be added into the draft of the criminal procedure code. With the intent to rectify the existing legal lacunae, this article discusses the above shortcomings and addresses the existing disharmony between criminal law and criminal procedural law and how to fill in the legal gaps. The author's main arguments are, taking in consideration the necessity to harmonize substantive and procedural law, first, that the legislature should synchronize-harmonize internally and externally the academic draft of the draft criminal procedure law and with the existing criminal code. Secondly, in the draft criminal procedure code should be added a ruling making the passing of judicial pardon a possibility. Third, to add a ruling obligating judge who pass such sentences to adequately support his/her decisions with arguments. Lastly, to add another ruling elaborating on for what crimes would judicial pardon be allowed and to what extent such sentences would be eligible to be challenged